Peran Guru PAI dalam Meningkatkan Kemampuan Membaca Al-Qur’an pada Siswa Kelas VII.2 di SMPN 42 Padang - Azizah, Nur; Ikhlas, Al (TSAQOFAH, 2025)
The low listening skills of elementary school students are often caused by conventional teaching approaches and the lack of varied techniques that encourage active engagement and effective learning. Furthermore, limitations in processing auditory information negatively affect comprehension of orally delivered material. This study aims to describe the improvement of students’ listening skills through the implementation of the Dictogloss technique. The research employed Classroom Action Research (CAR) in two cycles, comprising the stages of planning, implementation, observation, and reflection. The subjects were 12 fifth-grade students at UPTD SD Negeri 01 Andiang, Lima Puluh Kota Regency. A mixed-method approach, combining qualitative and quantitative data, was used. The results showed a significant improvement in listening skills, with the average score for the teaching module increasing from 85.71% to 96.42%, teacher performance from 79.16% to 95.83%, and student participation from 75% to 95.83%. Students’ listening skills also improved from 74.29% in the first cycle to 90.23% in the second cycle. These findings confirm that the Dictogloss technique is effective in enhancing listening abilities among elementary students. The study underscores the importance of using innovative instructional techniques to improve auditory literacy competencies at the primary education level.